PENGARUH BAURAN PROMOSI TERHADAP TINGKAT PENJUALAN PETANI PADA APLIKASI E-COMMERCE âE-FARMER FOR ANDROIDâ - Novianti, desi -; mufti, abdul; anjani, dewi (RABIT, 2018)
This study aimed to find out the influence of the promotional mix toward sales levels with the study on farmers to support the sale of agricultural output. The application of E-commerce E-Farmer For Android is a media promotion and information are expected to meet the needs of farmers to market the results of his farm. This research using the method of survey respondents with the farmers who use the application e-commerce e-farmer for Android . Testing is done using simple regression analysis and test F to do a test of the hypothesis. The results obtained are the promotion of E-Commerce applications using E-Farmer for Android "effect simultaneously against the level of sales